To solve the equation \(-2x + 3x - 1 = -2\), we first simplify and rearrange the equation:
\[ -x - 1 = -2 \]
Next, we add 1 to both sides:
\[ -x = -2 + 1 \]
Simplifying the right side gives:
\[ -x = -1 \]
Now, by multiplying both sides by -1:
\[ x = 1 \]
This is a linear equation, and therefore it does not produce a quadratic solution. However, you mentioned using the quadratic formula, which is typically applied to equations of the form \(ax^2 + bx + c = 0\).
If your goal is to apply the quadratic formula here simply as part of a request or just to gain clarity over other equations, please provide an appropriate quadratic equation (in the form \(ax^2 + bx + c = 0\)), and I can assist in solving that using the quadratic formula.
For the current equation, the final answer is:
\[ x = 1 \]
If you needed a different question or context, feel free to specify!